Influence of substitution and different role positions on metabolic power and high-intensity actions in professional soccer players - Laterza, F.; Savoia, C.; Bovenzi, A.; D`Onofrio, R.; Pompa, D.; Manzi, V. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Knowing the physical demands of the official matches is pivotal in every sport. In team sports, such as soccer, different role positioning, and strategical substitutions could make unclear how different physical capacities decrease over time and impact performance. The main limitations of previous studies were the limited number of athletes and data often referred to only one professional team. High-intensity actions are linked to the crucial moment of the match (1); consequently, focusing on these actions is essential. The present investigation aimed to analyze how different cinematic parameters change over game time and provided helpful information to prescribe more effective training programs. METHODS: Data from four professional teams competing in the Premier Division championship (Series A) were analyzed. The cinematic variables analyzed were average metabolic power (AP) and variables of high-intensity activities. Specifically, the number of power events per minute (PEm), distance (m) covered at (P>25watt/kg) x min-1 (D25), distance (m) covered at (5.28m/s<v6.94m/s) x min-1 (VHV) were analyzed as high-intensity assessments. All the data were collected by the validated multicamera video analysis system STATS SportVU during official matches for each team. Players were organized into seven groups based on the duration of their gameplay. Each player was assigned to a specific group according to their time played, categorized as follows: 0-15 min, 15-30 min, 30-45 min, 45-60 min, 60-75 min, 75-90 min, and more than 90 min (overtime was not considered). Additionally, different role-positioning, including forwards and wingers (FW), midfielders (MF), center-backs (CB), and left and right-backs (LR), were also contemplated. RESULTS: Significant differences (p < 0.05) were observed for cinematic variables analyzed among different role positions and within the same role across different gameplay durations. The results highlighted a gradual decrease in MFs` performance over time, as evidenced by higher performance values at shorter gameplay durations. In contrast, center-backs displayed a non-consistent pattern, showing no significant impact from time played. MFs also exhibited higher values of average metabolic power (AV) and power events per minute (PEm) compared to other roles, with medium and large effect sizes. Left and right backs and forwards spent more time at very high velocity (VHV) speeds than other roles, independently from the time played. CONCLUSION: These findings give helpful information about the physical demands required in an official soccer game, and coaches could use these data to review their training prescriptions.